VR's EFFICACY IN IMPROVING UPPER EXTREMITY MOTOR FUNGCTION IN STROKE PATIENTS - Simangunsong, Wilson; Kariasa, I Made (LPPM Universitas Prima Nusantara Bukittinggi, 2023)
Background: Stroke remains the second leading cause of death and the third combined cause of death and disability expressed by disability-adjusted lost life years (DALYs) in the world. Technological developments are used to provide more personalized and precise health services and are used for stroke prevention.Purpose: The purpose of this literature review is to look at the Effectiveness of Increasing Upper Extremity Motor Function Based on Vertual Reality Technology in Stroke Patients.Methods: The method used in the search for articles is database: Clinicalkey Nursing, EBSCOhost, EMBASE, ProQuest, Sage Journal, ScienceDirect, Scopus, SpringerLink and ClinicalKey.Results: Based on a literature review of 5 selected articles, it was found that virtual reality is effective for improving upper extremity motor function in stroke patients.Conclusion: Stroke patients can use virtual reality as a therapy to improve upper extremity motor function.